2016
DOI: 10.1159/000446241
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lactase Persistence Genotypes with High Intake of Dairy Saturated Fat and High Prevalence of Lactase Non-Persistence among the Mexican Population

Abstract: Background/Aim: Lactase (LCT) -13910 C>T and -22018 G>A polymorphisms associated with the lactase non-persistence (LNP)/persistence (LP) phenotypes vary globally. LP has been associated with obesity in Europeans. However, it has not been genetically evaluated in Mexico, a country with admixed population, recent introduction of dairy, and a high prevalence of obesity. Thus, we aimed to determine the distribution of the LCT polymorphisms and their association with the nutritional profile of West Mexico's populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The traditional Mexican diet improved insulin sensitivity (HOMA-IR), lowered serum concentrations of insulin-like growth factor-binding protein-3 (IGFBP-3), and tended to reduce concentrations of insulin-like growth factor-1 (IGF-1) under conditions of weight stability, while no difference in inflammatory response was revealed. However, that diet incorporated full-fat milk, which was one of the foods discarded in our study due to the high prevalence of the lactase non-persistence genotype in Mexico [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The traditional Mexican diet improved insulin sensitivity (HOMA-IR), lowered serum concentrations of insulin-like growth factor-binding protein-3 (IGFBP-3), and tended to reduce concentrations of insulin-like growth factor-1 (IGF-1) under conditions of weight stability, while no difference in inflammatory response was revealed. However, that diet incorporated full-fat milk, which was one of the foods discarded in our study due to the high prevalence of the lactase non-persistence genotype in Mexico [15].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the regionalized GENOMEX diet was designed considering some DRAG polymorphisms [9] that in modern dietary and lifestyle environments have been associated with increased risk of unhealthy conditions [10][11][12][13][14][15][16]. Accordingly, we assumed that carriers of the adaptive alleles might require nutritional needs related to the main features of the pre-Hispanic diet (i.e., milk-free, scarce in animal meat, low in saturated fat and cholesterol, with low glycemic index and rich in antioxidants, fiber, and micronutrients such as folates due to the abundance of starchy foods, legumes, vegetables, and fruits).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mestizo population comprise a variable proportion of AM, European (EUR) and African ancestry depending on the geographic region [ 21 ]. For instance, Central West (CW) Mexico harbors a heterogeneous population, with ethnic groups having a high amount of AM ancestry and Mestizos having an intermediate AM ancestry or predominantly EUR ancestry (Mestizos-EUR) [ 22 , 23 , 24 ]. This recent genetic admixture explains the presence in Mexicans of DRAG polymorphisms identified in other populations worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in the Mexican population have revealed a higher prevalence of risk alleles of sweet (TAS1R2)[107], fat (CD36)[108,109] and bitter (TAS2R38)[110] taste receptors, lipid-transporting proteins (APO e2 and e4, FABP2)[111], lactose intolerance (LCT-13910 C>T)[112] and neurotransmitter transporters (DRD2 Taq1)[113]. These alleles have been associated with metabolic abnormalities, obesity and alcohol abuse disorders, aggravated by the consumption of a hepatopathogenic and obesogenic diet[114].…”
Section: Genes-emotions-gut Microbiota Interaction: Regaining Health mentioning
confidence: 99%